COVID-19 Infections in Cancer Patients Were Frequently Asymptomatic: Description From a French Prospective Multicenter Cohort (PAPESCO-19). (April 2022) - Zhou, Ke; Raoul, Jean-Luc; Blanc-Lapierre, Audrey; Seegers, Valérie; Boisdron-Celle, Michèle; Bourdon, Marianne; Mahammedi, Hakim; Lambert, Aurélien; Moreau-Bachelard, Camille; Campone, Mario; Conroy, Thierry; Penault-Llorca, Frédérique; et al.
Background: Cancer patients (CPs) are considered more vulnerable and as a high mortality group regarding COVID-19. In this analysis, we aimed to describe asymptomatic COVID (+) CPs and associated factors. Methods: We conducted a prospective study in CPs and health care workers (HCWs) in 4 French cancer centers (PAPESCO [ PAtients et PErsonnels de Santé des Centres de Lutte Contre le Cancer pendant l'épidémie de COvid-19 ] study). This analysis used data recorded between June 17, 2020 and November 30, 2020 in CPs (first 2 waves, no variants). At inclusion and quarterly, CPs reported the presence of predefined COVID-19 symptoms and had a blood rapid diagnostic test; a reverse transcription polymerase chain reaction (RT-PCR) was done in case of suspected infection. Results: A total 878 CPs were included; COVID-19 prevalence was similar in both CPs (8%) and HCWs (9.5%); of the 70 CPs (8%) who were COVID (+), 29 (41.4%) were and remained asymptomatic; 241/808 of the COVID (−) (29.8%) were symptomatic. 18 COVID (+) were hospitalized (2% of CPs), 1 in intensive care unit (ICU) and 1 died (0.1% of CPs and 2.4% of symptomatic COVID [+] CPs). Only the inclusion center was associated with clinical presentation (in Nancy, Angers, Nantes, and Clermont-Ferrand: 65.4%, 35%, 28.6%, and 10% CPs were asymptomatic, respectively). Conclusions: Seroprevalence of COVID-19 in CPs was similar to that observed in HCWs; mortality related to COVID-19 among CPs was 0.1%. More than 40% of COVID (+) CPs were asymptomatic and one third of COVID (−) CPs had symptoms. Only geographic origin was associated with the presence or absence of symptoms. Social distancing and protective measures must be applied in CPs at home and when hospitalized.